2020
DOI: 10.1038/s41598-020-63014-7
|View full text |Cite
|
Sign up to set email alerts
|

Parity is associated with cognitive function and brain age in both females and males

Abstract: previous studies of the association between parity and long-term cognitive changes have primarily focused on women and have shown conflicting results. We investigated this association by analyzing data collected on 303,196 subjects from the UK Biobank. We found that in both females and males, having offspring was associated with a faster response time and fewer mistakes made in the visual memory task. Subjects with two or three children had the largest differences relative to those who were childless, with gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 34 publications
19
70
1
Order By: Relevance
“…This evidence of structural neuroprotection of parenthood has also been found in males [15]. In addition, middle-aged parents in the UK Biobank have faster response times and fewer errors on visual memory tasks than childless men and women [15].…”
Section: Introductionsupporting
confidence: 52%
“…This evidence of structural neuroprotection of parenthood has also been found in males [15]. In addition, middle-aged parents in the UK Biobank have faster response times and fewer errors on visual memory tasks than childless men and women [15].…”
Section: Introductionsupporting
confidence: 52%
“…That is, parents showed "younger-looking" brains with increasing number of children, suggesting a neuroprotective effect of parenthood on brain-age. In addition, middle-aged parents have faster response times and fewer errors on visual memory tasks than childless men and women (Ning et al, 2020). In healthy older adults aged over 70-years, we reported that cortical thickness differs between parents and non-parents of both sexes (Orchard et al, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…Taken together, current evidence is indicative of a life-long effect of parenthood on the human brain, which, at least in mothers, may be neuroprotective in ageing (de Lange et al, 2019;Ning et al, 2020;Orchard et al, 2020).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations